THE DEVELOPMENT MODEL OF COMMUNITY-BASED TOURISM IN NAGARI KOTO SANI, SOLOK REGENCY, WEST SUMATRA - Nofrion Nofrion; Sulis Purwanto; Erwin Pri Utomo; Saddam Al Aziz (GeoEco, 2023)
The development of a community-based tourism village gives wider authority to the community to manage the potential of their village and has an impact on improving the economy and sustainable development. The purpose of this research was to find a community-based tourism development model in Nagari Koto Sani which has natural and cultural potential as a tourism village. This qualitative approach of research collects data through observation, interviews, focused discussions and documentation studies. The data is then analyzed using qualitative analysis with triangulation, so that the data obtained is valid and saturated. The results of the research show that the development model of community-based tourism village consists of three main stages, i.e., planning, implementation and reflection. Activities at the planning stage include, 1) identification of the potential of the village (Nagari), 2) focused discussions regarding the views and aspirations of the community, 3) preparation of the RIPPDES draft, 4) focused discussions regarding familiarization of the tourism village program. Then, the activities at the implementation stage are 1) community awareness, 2) strengthening local resources, 3) cooperation between stakeholders, and 4) tourism village promotion. Finally, at the reflection stage, the activities carried out are 1) observation and monitoring, 2) follow-up plans.